Selfie Aging Index: An Index for the Self-assessment of Healthy and Active Aging - Gonçalves, Judite; Gomes, Maria Isabel; Fonseca, Miguel; Teodoro, Tomás; Barros, Pedro Pita; Botelho, Maria-Amália (Frontiers in Medicine, 2017)
Introduction: Governments across Europe want to promote healthy and active ageing, as a matter of both public health and economic sustainability. Designing policies focused on the most vulnerable groups requires information at the individual level. However, a measure of healthy and active ageing at the individual level does not yet exist. Objectives: This paper develops the Selfie Ageing Index (SAI), an individual-level index of healthy and active ageing. The SAI is developed thinking about a tool that would allow each person to take a selfie of her ageing status. Therefore, it is based entirely on self-assessed indicators. This paper also illustrates how the SAI may look like in practice. Methods: The SAI is based on the Bio-psycho-social Assessment Model (MAB), a tool for the multidimensional assessment of older adults along three domains: biological, psychological, and social. Indicators are selected and their weights determined based on an ordered probit model that relates the MAB indicators to self-assessed health, which proxies healthy and active ageing. The ordered probit model predicts the SAI based on the estimated parameters. Lastly, predictions are rescaled to the 0-1 interval. Data for the SAI development come from the Study of the Ageing Profiles of the Portuguese Population and the Survey of Health, Ageing and Retirement in Europe. Results: The selected indicators are BMI, having difficulties moving around indoors and performing the activities of daily living, feeling depressed, feeling nervous, lacking energy, time awareness score, marital status, having someone to confide in, education, type of job, exercise, and smoking status. The model also determines their weights. Conclusion: Results shed light on various factors that contribute significantly to healthy and active ageing. Two examples are mental health and exercise, which deserve more attention from individuals themselves, healthcare professionals, and public health policy. The SAI has the potential to put the individual at the center of the healthy and active ageing discussion, contribute to patient empowerment and promote patient-centered care. It can become a useful instrument to monitor healthy and active ageing for different actors, including individuals themselves, healthcare professionals, and policy makers.